The Ideal Legal Protection of the Child Labor Rights in Indonesia: The Dimensions of Maqāṣid al-Sharī‘ah and the Welfare State - Muhamad Harun; Fauziah Fauziah; Muhamad Sadi Is; Abdul Basir Bin Mohamad; Abdul Haq Syawqi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The legal protection of child labor rights in Indonesia, which is regulated in the Indonesian legislation, was not yet ideal. There are many working children (aged 13 to 15 years) in Indonesia whose rights to a prosperous life have not been fulfilled, both in the maqāṣid al-sharī‘ah dimension and in the welfare state dimension. Thus, this research was about the ideal legal protection for the rights of child workers in Indonesia, and the aim was to know and look for the concept of ideal legal protection for the rights of child workers of 13-15 years of age in Indonesia which was in accordance with maqāṣid al-sharī‘ah and the welfare state. This normative research discussed the constitution and laws related to child labor rights by examining the main legal materials, theories, concepts and legal bases related to this research. The results of this research explained that the legal protection of child labor rights in Indonesia was not yet ideal due to lack of clarity in the labor law itself. Meanwhile, the findings in this research; legal protection for the rights of child workers aged 13 to 15 years in Indonesia was not yet ideal because it was not yet in accordance with the dimensions of maqāṣid al-sharī‘ah and the welfare state, and because child labor in Indonesia was still considered unlawful, therefore many children in Indonesia became neglected and poor.